2017
DOI: 10.5430/ijhe.v6n2p162
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Correlation of the Improvement of Teaching Evaluation Scores Based on Student Performance Grades

Abstract: The purpose of the study is to explore the influence of teaching evaluations on teachers in that they might try to please their students by giving higher grades in order to get higher teaching evaluation scores. To achieve this purpose, the study analyzed the correlations between teaching evaluation scores, student's final grades and course fail rates, and it also examined whether students' final scores and course fail rates are important predictors of teaching evaluation scores. The study used teaching evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Consistent with our findings and reports of decreases on average study time (Babcock & Marks, ), increased academic effort also does not appear to be the cause (Katsikas, ). A number of potential reasons have been proposed for grade inflation, including the view of students as consumers who should be kept happy, the need for departments to keep enrollments high, and the desire of professors for positive teaching evaluations that can impact job security (Chen, Wang, & Yang, ; Nikolakakos et al, ). Though we were unable to determine if the GPA at the participant institutions has been increasing, our results suggested that students are earning strong grades with far less effort than is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings and reports of decreases on average study time (Babcock & Marks, ), increased academic effort also does not appear to be the cause (Katsikas, ). A number of potential reasons have been proposed for grade inflation, including the view of students as consumers who should be kept happy, the need for departments to keep enrollments high, and the desire of professors for positive teaching evaluations that can impact job security (Chen, Wang, & Yang, ; Nikolakakos et al, ). Though we were unable to determine if the GPA at the participant institutions has been increasing, our results suggested that students are earning strong grades with far less effort than is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize: Hypothesis 6: Metacognitive skills have a positive relationship with app delivery. Grades of students serve as a measure of performance and achievement in higher education (Zajacova et al, 2005). Universities use grades as a decision criterion for failing or passing a course (Chen et al, 2017). Similarly, employers and stipend institutions use grades when deciding about hiring or funding a graduate (Humburg & Van der Velden, 2015; Petzold, 2017).…”
Section: Study 1: Impact On Metacognitive Skills and Learning Outcome...mentioning
confidence: 99%
“…However, graduates need to be able to convey their human capital to potential employers, particularly as suggestions of grade inflation reduce the value of the degree classification as a differentiator of talent (Bachan, 2017;Chen et al, 2017). Consequently, the graduate premium can be attributed to a combination of human capital and signalling (Rospigliosi et al, 2014).…”
Section: Human Capital and Signalling Employabilitymentioning
confidence: 99%